2022
DOI: 10.54167/tecnociencia.v16i2.953
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de factores de concentración en la calidad del agua subterránea en el norte-centro de México

Abstract: Se analizaron datos de calidad de agua subterránea de los estados de Chihuahua, Coahuila y Durango (N=704) para determinar la distribución de tres contaminantes comúnmente presentes en el área, arsénico (As), fluoruro (F), y nitrato (NO3-N), y determinar el efecto de factores de enriquecimiento. Dichos factores incluyen evaporación, intemperismo de rocas, HCO3, y solidos disueltos totales (SDT). Se construyeron mapas de concentración y se obtuvieron correlaciones para contaminantes entre sí, así como entre los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Clwas another element that exceeded the maximum permissible limits. Gutiérrez et al (2022) indicated that irrigating with water with high Clcontent, can be detrimental to soil micro fauna, in addition to having a deleterious effect on roots, inhibiting nutrient uptake. Alcívar et al (2017) in their research in Ecuador in well water samples, reported values above the maximum limit allowed by TULSMA, such as hardness, total dissolved solids, ammonium, aluminum and nitrates.…”
Section: Physical Chemical and Microbiological Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clwas another element that exceeded the maximum permissible limits. Gutiérrez et al (2022) indicated that irrigating with water with high Clcontent, can be detrimental to soil micro fauna, in addition to having a deleterious effect on roots, inhibiting nutrient uptake. Alcívar et al (2017) in their research in Ecuador in well water samples, reported values above the maximum limit allowed by TULSMA, such as hardness, total dissolved solids, ammonium, aluminum and nitrates.…”
Section: Physical Chemical and Microbiological Analysesmentioning
confidence: 99%
“…For Gutiérrez et al (2022), groundwater is an important source of water for human consumption, crop irrigation, industrial use, among others, but it is becoming an increasingly scarce resource. The assessment of groundwater quality becomes relevant for activities that require its use, especially agriculture, which, according to the Statistics Division of the Food and Agriculture Organization of the United Nations [FAOSTAT] (2018), accounts for 70 % of the freshwater withdrawn in the world.…”
Section: Introductionmentioning
confidence: 99%